A systemic review of taxanes and their side effects in metastatic breast cancer - Lai, Jiun-I.; Chao, Ta-Chung; Liu, Chun-Yu; Huang, Chi-Cheng; Tseng, Ling-Ming (Frontiers in Oncology, 2022)
Taxanes-containing chemotherapy constitutes an essential backbone for both early and metastatic breast cancer (mBC). However, the two major taxane drugs—paclitaxel and docetaxel—have distinct safety profiles. In this review, we summarize the safety outcome and management following treatment with both taxanes from selected clinical trials. We utilized PubMed to perform literature search before April 2021. Five phase III randomized controlled trials with reports of individual taxane adverse events (AEs) were included in this review. Grade 3/4 AEs were summarized and discussed extensively. The rates of grade 3/4 neutropenia were higher with docetaxel than with paclitaxel. For non-hematologic grade 3/4 AEs, peripheral neuropathy was more frequent with paclitaxel while fluid retention was more frequent with docetaxel. Compared to paclitaxel, docetaxel had a higher rate of grade 3/4 gastrointestinal AEs. Grade 3/4 myalgia were generally comparable between the two taxanes. Except for neutropenia, the incidence rate of grade 3/4 AEs of taxanes was generally manageable. Peripheral neuropathy was more common with paclitaxel while grade 3/4 neutropenia was more common with docetaxel.